Navigating Across Non-Navigable Ecore References via OCL - Hanysz, Martin; Hoppe, Tobias; Uhl, Axel; Seibel, Andreas; Giese, Holger; Berger, Philipp; Hildebrandt, Stephan (Electronic Communications of the EASST, 2010)
The Eclipse Modeling Framework (EMF) and its meta-meta model Ecore support uni-directional and bi-directional references. It is quite common that references are defined uni-directionally only because of saving storage space or separating meta models, which is problematic when implementing Object Constraint Language (OCL) constraints that require navigation against the direction of uni-directional references. This is essential for certain approaches, e.g., incremental evaluation of OCL constraints on models shown by Altenhofen et al. that is used in SAP’s Modeling Infrastructure (MOIN). In this paper, we present an approach that overcomes the aforementioned issue by providing navigation across non-navigable Ecore references via OCL. We further discuss different alternative solutions and briefly describe the realization that was outcome of a project in cooperation with the SAP AG.